Efektivitas Short Wave Diathermy Terhadap Penurunan Nyeri Dan Exercise Punggung Bawah:Literatur Review - Dhendra Bhima Agastya; Dini Nur Alpiah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Low Back Pain (LBP) is the most common musculoskeletal condition with a high global disability impact. Short-Wave Diathermy (SWD) is a deep-heating modality frequently used to reduce pain and increase tissue extensibility. The purpose of this literature review is to evaluate the effectiveness of SWD, either independently or in combination with therapeutic exercises, on reducing pain intensity and improving function in chronic LBP patients. This research uses a literature review design with article searches from databases such as PubMed, Google Scholar, and ScienceDirect. A total of 10 relevant research journals were analyzed, most of which used a Randomized Controlled Trial (RCT) design. The analysis results show that SWD application provides a significant analgesic effect (p < 0.05) through nociceptive system modulation and microcirculation enhancement. The combination of SWD with active exercises such as Pilates or dynamic stretching provides more optimal short-term and medium-term results compared to monotherapy. In conclusion, SWD is an effective and safe modality as part of a comprehensive rehabilitation management for LBP sufferers.